Analysis of Student’s Ability in Creative Thinking on Entrepreneurship Learning at Class IV SDN 3 Krakal - Usvah Istkomah; Kartika Chrysti Suryandari (Universitas Sebelas Maret, 2019)
This study aims to analyze the ability of students in creative thinking in entrepreneurial learning class IV Krakal 3 Elementary School 2019/2020. The design of this research is simple descriptive. The object of research is the ability to think creatively in entrepreneurial learning with indicators of fluency thinking, flexible thinking, original thinking and elaborative thinking. The research subjects were grade IV students with 20 students. Data analysis was performed using descriptive techniques and existing data in the form of qualitative data from observation sheets and student questionnaires which were then described. The results showed that overall creative abilities included thinking fluency that was already good with a percentage of 78.75%, flexible thinking also showed quite good results with a percentage of 64.37%, Original Thinking was categorized quite well with a percentage of 68.12%, and Thinking Elaborative categorized quite well with a percentage of 70.62%. This shows that students are able to think creatively in entrepreneurship learning.